Rhythmic Gymnastics: Games for Stimulating Kinesthetic Intelligence in Early Children - Pahenra Pahenra; Zulaeni Eshita; Wa Ode Sari Amalia; Sitti Salma; Nurhalizah Nurhalizah (Universitas Negeri Semarang, 2024)
Kinesthetic intelligence is the ability to combine the physical and the mind to produce perfect movements. One method to improve children's kinesthetic intelligence is by playing rhythmic gymnastics games. This research aims to determine the increase in kinesthetic intelligence of early childhood in the Darussalam Kindergarten, Kendari city, using rhythmic gymnastics as a media game. The type of research is classroom action research which includes 2 cycles with 10 action assessment indicators. Data collection methods are carried out through observation, interviews and documentation. Based on the results of research conducted at the initial stage of the rhythmic gymnastics activity process by designing learning modules, preparing the media to be used, organizing classes to condition children. In the core activity, children begin to do rhythmic gymnastics activities. At the end of the activity the teacher held a discussion regarding the rhythmic gymnastics activities that had been carried out and held a reflection. The success indicator in this research is 75%. The results of the research show that children's kinesthetic intelligence can be improved through rhythmic gymnastics games. It is known that in the initial conditions or cycle 1, the child's success indicator only reached 46.67%. Then in cycle II it increased to 86.67%, this increased significantly. It can be concluded that rhythmic gymnastics games have succeeded in increasing the kinesthetic intelligence of early childhood in the Darussalam Kindergarten, Kendari City, therefore the research results can be used as a reference by early childhood education institutions to improve children's motor skills, especially children's kinesthetic intelligence